The Optimal Choice of Commuting Speed: Consequences for Commuting Time, Distance and Costs - Jos van Ommeren; Joyce Dargay (Tinbergen Institute, 2004)
In this paper, we derive a structural model for commuting speed. We presumethat commuting speed is chosen to minimise commuting costs, which encompass bothmonetary and time costs. At faster speed levels, the monetary costs increase, but the timecosts fall. Using data from Great Britain, we demonstrate that the income elasticity ofcommuting speed is 0.126. The ratio of variabIe monetary costs to travel time costs is0.14.
Keywords: R41; 330; commuting; speed; travel demand modelling; Pendelverkehr; Transportzeit; Einkommenselastizität; Großbritannien